Investigation of Effecting Parameters in a Turning Operation - Khleif, Ali Abbar; Elias, Rasha R.; Kashkul, Lujain Hussein (Al-Khwarizmi Engineering Journal, 2019)
In this study multi objective optimization is utilized to optimize a turning operation to reveal the appropriate level of process features. The goal of this work is to evaluate the optimal combination of cutting parameters like feed, spindle speed, inclination angle and workpiece material to have a best surface quality Taguchi technique L9 mixed orthogonal array, has been adopted to optimize the roughness of surface. Three rods of length around (200 mm) for the three metals are used for this work. Each rod is divided into three parts with 50 mm length. For brass the optimum parametric mix for minimum Ra is A1, B1 and C3, i.e., at tool inclination angle (5), feedrate of 0.01, spindle speed of 1200 rpm. For copper the optimal parameters combination for best Ra is A1, B1 and C3, i.e., at tool inclination angle (5), feedrate of 0.01, spindle speed of 1200 rpm. For bronze the optimum parameters mix for minimum Ra is A1, B1and C3, i.e., at tool inclination angle (5), feedrate of 0.01, spindle speed of 1200 rpm.